The Innovative Potential of Statins in Cancer: New Targets for New Therapies - Elisabetta Di Bello; Clemens Zwergel; Clemens Zwergel; Antonello Mai; Sergio Valente (Frontiers in Chemistry, 2020)
Numerous and different types of cancers possess the dysregulation of the mevalonate pathway as a common feature. Statins, traditionally applied in cardiovascular diseases to reduce lipid levels, subsequently have been discovered to exhibit anti-cancer activities also. Indeed, statins influence proliferation, migration, and survival of cancer cells by regulating crucial signaling proteins, such as Rho, Ras, and Rac. Recently, several studies have demonstrated that simvastatin, fluvastatin, and lovastatin are implicated in different pathways that enhance the survival time of patients with cancer under treatment in combination with antineoplastic agents. In this minireview, we present an overview of the most important studies conducted regarding the use of statins in cancer therapy up to date.